"THE STUDY OF LINGUISTIC EXPERTISE IN UZBEK LINGUISTICS" - Saidahmadov Shuhrat Baxtiyor ugli (International Journal of Literature and Language Studies, 2026)
This article examines the formation, content, and theoretical foundations of linguistic expertise, which is one of the promising directions of modern linguistics. The study analyzes the differentiation of the concepts of "linguistic expertise" and "linguistic expertology," as well as the role of texts, which are considered speech products, in legal and social expertise. Furthermore, the importance of the linguistic expert conclusion as evidence in judicial and extrajudicial proceedings and the socio-economic characteristics of this field are highlighted. The article is intended for specialists studying the integration of applied linguistics and jurisprudence.